2012
DOI: 10.1134/s1063778812020020
|View full text |Cite
|
Sign up to set email alerts
|

Precise calculations of observables of polarized møller scattering: From JLAB to ILC energies

Abstract: One-loop electroweak corrections to observables of the reaction e − e − → e − e − (γ) were calculated over a broad range of energies: from conditions of the MOLLER experiment at the Thomas Jefferson Laboratory (JLab) to those of planned experiments at the International Linear Collider (ILC). The dependence of various contributions to the observable polarization asymmetry on various renormalization conditions was studied within the scheme of on-shell renormalization. The results were obtained by two methods: pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The relative correction to observable asymmetry from the contribution of type C looks as (see derivation in more details in [19]):…”
Section: Basic Notationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative correction to observable asymmetry from the contribution of type C looks as (see derivation in more details in [19]):…”
Section: Basic Notationsmentioning
confidence: 99%
“…The significant theoretical effort has been dedicated to one-loop radiative corrections already. A short review of the references on that topic is done in [18,19], where we calculated a full set of the one-loop electroweak corrections (EWC) both numerically with no simplifications using computer algebra packages and by-hand in a compact form analytically free from nonphysical parameters, and found the total relative correction to the observable asymmetry to be close to −70%. It is possible that a large theoretical uncertainty in the prediction for the asymmetry may come from two-loop corrections.…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques have their advantages and limitations, but can be very powerful in a combination. Our earlier publications ( [15], [16], [17]) on (e − e − → e − e − scattering showed that the exact analytical one-loop calculations using the computer algebra approach not only increased the theoretical precision dramatically, but also gave us an opportunity to verify previous calculations done in various formalisms.…”
Section: Introductionmentioning
confidence: 99%
“…The significant efforts have been already dedicated to one-loop EWC. A short review of the references on that topic is given in [18,19], where we calculated a full set of the one-loop EWC both numerically with no simplifications using computer algebra packages and byhand in a compact form analytically free from nonphysical parameters. One way to find some indication of the size of higher-order (two-loop) contributions is to compare results that are expressed in terms of quantities related to different renormalization schemes.…”
Section: Introductionmentioning
confidence: 99%